PENINGKATAN PRODUKSI BAHAN BAKAR HIDROGEN DENGAN BANTUAN NATURAL SURFACTANT PADA PROSES WATER SPLIT - Purnami, Purnami; Dewi, Fransisca Gayuh Utami; Wardana, ING; Sasongko, Mega Nur; Yusuf, M Umar; Nugroho, Willy Satrio (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Hydrogen is an alternative fuel due to its environmental friendliness and abundance. Hydrogen can be produced through water-splitting technique, in which the Oxygen (O2) and Hydrogen (H2) are separated. Water electrolysis is one of many causes of water-splitting that effectively results H2 with high purity. One drawback of electrolysis is the low efficiency. In this study, a rice straw natural surfactant was utilized to improve the efficiency. Rice straw with the volume of 5 ml, 10 ml, dan 15 ml were added to the electrolyte solution. This study shows the rice straw based natural surfactant contains hydrophilic and hydrophobic sides. Both sides capable to reduce the surface tension of the solution which destabilizes water molecules. The aromatic magnetic field of rice straw surfactant homogenizes the water net dipole moment due to the diamagnetism of water. These contributes towards the weakened hydrogen bond of the water in the solution. The synergy between hydrophobic and hydrophilic sides is potent to alter hydrogen production rate through intrinsic magnetism.